Rare-earth metal compounds with a novel ligand 2-methoxycinnamylidenepyruvate: A thermal and spectroscopic approach - Carvalho, C. T.; Oliveira, G. F.; Fernandes, J.; Siqueira, A. B.; Ionashiro, E. Y.; Ionashiro, M. [UNESP] (Elsevier B.V., 2016)
Compounds of 2-methoxycinnamylidenepyruvate with trivalent lanthanide ions (Tb, Ho, Er, Tm, Yb and Lu) were obtained in solid state and studied mainly in terms of their thermal and spectroscopic properties. The analyses of the characterization were performed by thermogravimetric system coupled to a mass and infrared spectrometer (TG-DTA/MS and TG-DTA/FT-IR), X-ray powder diffractometry, differential scanning calorimetry (DSC), infrared (FT-IR), preliminary study of fluorescence as well as classical technique of titration with EDTA. From these results, it was possible to establish the stoichiometry, thermal behavior, hydration water content, and the gaseous products released in the thermal decomposition steps, and suggest the type of metal-ligand coordination. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Lanthanide; 2-Methoxycinnamylidenepyruvate; Compounds; TG-DTA/FT-IR; TG-DTA/MS